Effect of Planting System on Productivity of Hybrid Maize-Indian Spinach Intercropping System (Bangladesh Agronomy Journal, 2022)
A field experiment was undertaken at Joydebpur, Jashore and Ishurdi Farm of Bangladesh Agricultural Research Institute during Kharif seasons of 2016 and 2017 to find out suitable combination of hybrid maize and Indian spinach as intercropping system for higher productivity and monetary advantage. Treatments included in the experiment were: T1 = Hybrid maize normal row (75 cm × 20 cm ) + 1 row Indian spinach (plant to plant 25 cm), T2 = Hybrid maize paired row (37.5 cm/150 cm × 20 cm) + 1 row Indian spinach (plant to plant  25 cm), T3 = Hybrid maize paired row (37.5 cm/150 cm × 20 cm) + 2 rows Indian spinach (plant to plant 25 cm), T4 = Hybrid maize paired row (37.5 cm/150 cm × 20 cm) + 3 rows Indian spinach (plant to plant 25 cm), T5 = Sole maize (75 cm × 20 cm) and T6 = Sole Indian spinach (40 cm × 25 cm). Grain yield of maize was the maximum in sole crop but it was decreased 1.0 to 12.6% at Joydebpur, 5.2 to 17.1% at Jashore and 13.4 to 22.2% at Ishurdi due to inter specific competition for growth resources among maize and Indian spinach due to intercropping. All intercropping treatments showed better performance than sole maize crop. The highest maize equivalent yield (19.22 and 18.80 t ha-1 at Joydebpur, 13.30 and 11.58 t ha-1 at Jashore and 11.23 and 11.10 t ha-1 at Ishurdi in 2016 and 2017, respectively),  gross margin (Tk. 196300 and Tk. 192000 ha-1 at Joydebpur, Tk. 111130 and Tk. 85330 ha-1 at Jashore and  Tk. 88450 and Tk. 86500 ha-1 at Ishurdi in 2016 and  2017, respectively) and benefit cost ratio (3.13 and 3.07 at Joydebpur, 2.26 and 1.97 at Jashore and 2.11 and 2.08 at Ishurdi in 2016 and 2017, respectively) were observed in hybrid maize paired row + 3 rows Indian spinach intercropping. The highest land equivalent ratio (1.32 and 1.39 at Joydebpur and 1.50 and 1.47 at Jashore in 2016 and 2017, respectively) was also found in the same treatment. On the other hand, at Ishurdi, the highest LER (1.34 and 1.35 in 2016 and 2017, respectively) was observed in MNR + 1 rows ISP treatment followed by MPR + 3 rows ISP treatment. The results revealed that hybrid maize paired row + 3 rows Indian spinach and Hybrid maize normal row + 1 row Indian spinach intercropping might be economically profitable for hybrid maize + Indian spinach intercropping system at Joydebpur, Jashore and Ishurdi.Bangladesh Agron. J. 2022, 25(1): 75-82